Quantitative and Qualitative Analysis of Highly Cited Papers from India on Academic Libraries Research during 2001-2024 - Gupta, Brij Mohan; Verma, Manoj Kumar; Kappi, Mallikarjun; Tripathi, Manorama; Mamdapur, Ghouse Modin Nabeesab (Journal of Data Science, Informetrics, and Citation Studies)
Academic libraries are central to higher education, supporting teaching, learning, and research by providing access to diverse resources and promoting information literacy and community engagement. This study examines highly cited publications to identify key trends and focal areas in India’s academic library research. Data were retrieved from the Scopus database for the period 2001-2024 using a targeted keyword strategy. A total of 112 highly cited documents (each with six or more citations) were analyzed. The Bibliometrix package in R was used for quantitative analysis, and VOSviewer was employed for network visualization. Findings reveal growth in annual publications, evolving citation patterns, and the active contributions of leading countries, institutions, authors, journals, and keywords. This study provides valuable insights into India’s academic library research landscape and offers a framework to enhance scholarly quality and collaboration.